Development of Animation-Based Fairy Tales Learning Model for Elementary School Students - Sunarti, Sunarti; Rahmawati, Selly; Wardani, Setia (Proceeding International Conference on Science and Engineering, 2017)
The purpose of this research is developing an animation-based fairy tale as a teaching model for elementary students.In addition, this study is also intended to determine the effectiveness of animation-based fairy tale as a teaching model. This research type is research of development with subject is elementary students in SD Sonosewu. Methods of data collection used observation, questionnaires and tests. The data analysis technique to be used is quantitative approach with t-test independent sample. Output targets to be generated in the study are: (1) Design of animation-based fairy tales for elementary students developed with 6 steps of research and development i.e. research and gathering, planning, product draft development, initial field trials, revising test results and field trials. (2) An animation-based fairy tale model is effective in improving Civics achievement and Indonesian achievement.